2019
DOI: 10.1186/s13049-019-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient and rescuer safety: recommendations for dispatch and prioritization of rescue resources based on a retrospective study of Norwegian avalanche incidents 1996–2017

Abstract: BackgroundAvalanche emergency response should address current accident scenarios to optimize survival chances of victims and to keep rescuers safe. The purpose of this article is to present a basis for evaluation and necessary adjustments in dispatch, prioritization, and management of Norwegian avalanche rescue operations.MethodsThis is the first peer-reviewed retrospective study of all Norwegian avalanche incidents registered by the two Joint Rescue Co-ordination Centers (JRCCs) in the period 1996–2017 that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…130 Conditions such as inclement weather and pilot proficiency in mountain environments can significantly affect helicopter performance and safety. 119,131 Recommendations. We suggest professional rescue teams should only use helicopters with crews specifically trained in avalanche rescue, if possible.…”
Section: Professional Rescuementioning
confidence: 99%
See 1 more Smart Citation
“…130 Conditions such as inclement weather and pilot proficiency in mountain environments can significantly affect helicopter performance and safety. 119,131 Recommendations. We suggest professional rescue teams should only use helicopters with crews specifically trained in avalanche rescue, if possible.…”
Section: Professional Rescuementioning
confidence: 99%
“…130 Conditions such as inclement weather and pilot proficiency in mountain environments can significantly affect helicopter performance and safety. 119,131…”
Section: Rescuementioning
confidence: 99%
“…The results from this study indicate that they do not meet the expectations laid down in instructions (Regjeringen, 2013; and guidelines (NRR, 2012). This contributes to a deficient control of rescue operations in the critical first hour, and a suboptimal dispatch and prioritization of rescue resources could affect the survival chances of avalanche victims (Lunde & Tellefsen, 2019).…”
Section: Failing Assumptionsmentioning
confidence: 99%
“…In many of these situations, it is uncertain whether victims are involved in the avalanche or not, and high-risk search operations may be initiated without clear indications of a critical situation (Lunde & Njå, 2019). In a recent survey, it was found that fifty percent of all recorded Norwegian avalanche rescue operations in the period 1996-2017 involved no victims (Lunde & Tellefsen, 2019). This high number of rescue operations with no human victims puts an extra burden on the rescue services and their representatives.…”
Section: Introductionmentioning
confidence: 99%
“…Refuse: HEMS teams in search and rescue missions are frequently deployed for the assessment of the scene safety of ground-based personnel in unclear and difficult-to-reach areas. For example, 50% of the avalanche rescue operations in Norway did not involve any victims [ 4 ]. Drones could assist in the assessment of the scene, the patient search, and the delivery of medical equipment [ 5 ].…”
mentioning
confidence: 99%